Psychological testing : theory and practice - Cooper, Colin, ....- (London : Routledge, 2019)
I'd recommend this book to practising professionals as well as students. It's a useful reminder of procedures, as well as a clear exposition of the challenges... Overall, this book provides a thorough coverage of major procedures, and a helpful summary of significant controversial issues. It's also, in itself, an interesting read! - Nicky Hayes, Testing International Colin Cooper's book is a splendid synthesis of the theory, statistics and applications of psychometrics. We are taken on a journey through this measurement of the human spirit', spanning basic concepts (reliability/validity), workhorse statistics (factor analyses), more recent techniques (item response theory), how to interpret test scores and, even, how to develop scales. But there is more: this is a hands-on book - each chapter comes with a datasheet on which to practice newly-acquired knowledge of psychometrics. Students, lecturers, test developers and practitioners will delight in this charming book. - Professor Philip J Corr, City, University of London, UK What a gem of a book this is! I am delighted to recommend Colin Cooper's Psychological Testing: Theory and Practice to students, researchers, clinicians and educators. While the book eschews unnecessary diversions into mathematical and statistical obscurities, it also steers clear of the superficial, homespun presentations that sacrifice rigour in the altar of unrewarding readability. Without a doubt, this is one of the most accessible, effective and comprehensive introductions to psychological testing in the market today. - Professor K. V. Petrides, London Psychometric Laboratory, University College London, UK Colin Cooper has written the down-to-earth' book that many of us have been waiting for on the very complex and often misunderstood field of psychology tests and assessment.
Psychologische testen